Preliminary study on leech crude extract as an anti-coagulant agent - Zulhisyam Abdul Kari @ Abdullah; Ahmad Anwar Mohamed Ismail; Ibrahim Che Omar (2010)
Hirudin is the generic name for a family of closely related homologous peptides that are all found in the cranial salivary glands of medicinal leech (Wallis, 1996). In 1984, the blood-thinning agent (anticoagulant) hirudin was isolated for the first time from leech salivary glands (Weinnberg, 1994). Today, hirudin is the most specific and active of known thrombin inhibitors not influencing on other peptidases (Hofsteenge and Stone, 1987). Hirudinea sp. (Buffalo Leech) was used for the isolation of hirudin for anti-coagulant application. The leech crude extract was prepared by using conventional method and tested to fresh rabbit blood. The time of blood clotting was recorded by using a drop method (Prakasam et. al., 2005). Three replicates were applied for each treatment. The results showed that the rabbit blood treated with leech crude extract gave the longest time of blood to clot with average and standard deviation values of 15.33±0.6 minutes when compared to treatment with distilled water and that on blood only (control) with an average and standard deviation values of 2.83±0.3 and 0.59±0.01 minutes, respectively. These results revealed that crude extract of leeches contain an anticoagulant agent to prevent blood from clotting. The study on leech crude extract will be extended to include purification of hirudin for applications as anti-coagulant agent.